PENGARUH MEDIA PEMBELAJARAN PINTER TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN IPA KELAS VI DI SDN 1 PANAMBANGAN - Priatna, Dzela Putri; Huda, Muhamad Khozinul; Putra, Nugraha Permana (Cahaya Ilmu Bangsa Institute, 2024)
This study aims to find out the learning outcomes of students before the application of interactive power point learning media, to find out the learning outcomes of students after the application of interactive power point learning media, and to find out whether there is an effect of the use of power point learning media on the learning outcomes of science students in grade VI at SDN 1 Panambangan. The method in this study is to use a quantitative approach. The design in this study is a pre-experimental design experiment in one group of pretest-posttest design. The experimental class in this study was class VI of SDN 1 Panambangan with a total of 39 students. The data collection technique in this study is in the form of documentation and tests in the form of multiple-choice questions pretest-posttest. The data analysis techniques in this study are in the form of normality test testing, homogeneity test, and hypothesis test (paired sample t-test). The results in this study include: 1) the learning outcomes of students before being given the treatment had the highest score of 80 and the lowest score of 33 with an average score of 58.20. 2) The learning outcomes of students after being given the treatment had the highest score of 100 and the lowest score of 60 with an average score of 80. 3) There was an effect of the use of interactive power point learning media on student learning outcomes in science lessons on earth material and the season of grade VI SDN 1 Panambangan, this is evidenced by the results of the paired sample t-test which has a sig. (2-tailed) 0.000 < of 0.05, then Ho is rejected and Ha is accepted.